Sexual selection leads to a tenfold difference in reproductive success of alternative reproductive tactics in male Atlantic salmon - Tentelier, Cédric; Olivier Lepais; Nicolas Larranaga; Aurélie Manicki; Frédéric Lange; Jacques Rives (Die Naturwissenschaften, 2016)
The precocious maturation of some male Atlantic salmon (Salmo salar L.) has become a textbook example of alternative mating tactics, but the only estimates of reproductive success available so far are either the collective contribution of precocious males to reproduction in the wild or individual reproductive success in oversimplified experimental conditions. Using genetic parentage analysis on anadromous and precocious potential spawners and their offspring, we quantified components of individual reproductive success of both tactics in a natural population. On average, precocious males produced 2.24 (variance 67.62) offspring, against 27.17 (3080) for anadromous males. For both tactics, most of the variance in reproductive success was due to mating success, with 83Â % of precocious males having no mate, against 50Â % for anadromous males. Body size increased reproductive success of anadromous males and tended to decrease precocious malesâ reproductive success. Although these results do not solve the coexistence of alternative reproductive tactics (ARTs) in Atlantic salmon, their inclusion in comprehensive models of lifetime reproductive success should shed light on the evolution of precocious maturation in Atlantic salmon and its effect on the selection of phenotypic traits.